2020
DOI: 10.1155/2020/3916361
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Prehospital Delay among Men and Women Newly Experiencing Acute Coronary Syndrome: A Qualitative Inquiry

Abstract: Background. Delaying seeking health care for patients with acute coronary syndrome (ACS) causes high mortality and morbidity with variations among men and women regarding reasons for this delay. Objectives. This study explored factors associated with prehospital delay among men and women experiencing acute coronary syndrome for the first time in Jordan. Methods. 35 men and 33 women with ACS admitted and treated at the coronary and postcoronary care units. Results. Themes emerging from the data are knowledge ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…Timely identification and diagnosis of ACS could be challenging in clinical practice and community. Patients' prehospital delay can be due to lack of knowledge about the ACS symptoms, inability to interpret ACS symptoms, or confusion between ACS and other symptoms related to the upper respiratory or gastrointestinal tracts [48]. Moreover, women with ACS have longer patient delays, prehospital healthcare delays, hospital delays, and total healthcare delays [49].…”
Section: Discussionmentioning
confidence: 99%
“…Timely identification and diagnosis of ACS could be challenging in clinical practice and community. Patients' prehospital delay can be due to lack of knowledge about the ACS symptoms, inability to interpret ACS symptoms, or confusion between ACS and other symptoms related to the upper respiratory or gastrointestinal tracts [48]. Moreover, women with ACS have longer patient delays, prehospital healthcare delays, hospital delays, and total healthcare delays [49].…”
Section: Discussionmentioning
confidence: 99%
“…This can partially explain the high rate of inaccurate causal attributions made by participants and their delay in seeking medical help. A study in Jordan found that delay in the diagnosis and treatment of ACS was more common in first-time ACS patients than in those with previous ACS experience [ 22 ]. When women experience the warning or early symptoms of ACS for the first time, they may focus on symptom relief more than symptom attribution or try to understand the cause of their symptoms through developing various hypotheses.…”
Section: Discussionmentioning
confidence: 99%
“… 6 , 7 The varied pattern of accompanying symptoms makes it difficult for women to interpret their chest pain as being cardiac-specific. 8 , 9 , 10 Women also may minimize their symptoms, consult with family and friends, have caregiving responsibilities, and have concerns for their family 11 , 12 –as a result, they may delay seeking care for their chest pain. 13 In the International Survey of Acute Coronary Syndromes in Transitional Countries (ISACS-TC), the time from symptom onset to emergency department arrival was longer in women (median: 270 minutes [range: 130-776 minutes]) compared with that in men (median: 240 minutes [range: 120-600 minutes]), which resulted in increased 30-day mortality for women, even after controlling for baseline variables (odds ratio: 1.58; 95% confidence interval [CI], 1.27-1.97).…”
Section: Acute Presentations: Diagnosis and Treatmentmentioning
confidence: 99%